"(x+1)/(x-1) 미분"의 두 판 사이의 차이

15번째 줄: 15번째 줄:


<math>=\frac{-2}{(x-1)^2}</math>
<math>=\frac{-2}{(x-1)^2}</math>
<math>=-2(x-1)^{-2}</math>


==같이 보기==
==같이 보기==

2015년 10월 18일 (일) 10:55 판

1 개요

(x+1)/(x-1) 미분

[math]\displaystyle{ \left( \frac{x+1}{x-1} \right)' }[/math]

[math]\displaystyle{ =\left\{ (x+1)(x-1)^{-1} \right\}' }[/math]

[math]\displaystyle{ =(x+1)' \cdot (x-1)^{-1} + (x+1) \cdot \left\{ (x-1)^{-1} \right\}' }[/math]

[math]\displaystyle{ =\frac{ (x+1)' }{ x-1 } + (x+1) \cdot \left\{ -1 \cdot (x-1)^{-2} \right\} }[/math]

[math]\displaystyle{ =\frac{ 1 }{ x-1 } - \frac{ x+1 }{(x-1)^2} }[/math][1]

[math]\displaystyle{ =\frac{x-1-(x+1)}{(x-1)^2} }[/math]

[math]\displaystyle{ =\frac{-2}{(x-1)^2} }[/math]

2 같이 보기

3 참고 자료

  1. 통분